Responsive Polypseudorotaxane Hydrogels Triggered by a Compatible Stimulus of CO2. Issue 12 (9th May 2019) - Yan, Diwei; Liu, Sa; Jia, Yong‐Guang; Mo, Lina; Qi, Dawei; Wang, Jin; Chen, Yunhua; Ren, Li
Abstract: Realizing the reversible transformation of the supramolecular hydrogels is essential for their application as smart materials. The reversible sol‐gel transition of the polypseudorotaxane (PPR) hydrogels is achieved through adding a CO2 ‐switchable guest molecule into the PPR hydrogel of poly(ethylene glycol) (PEG) and α‐cyclodextrins (α‐CDs). Alternating treatments with CO2 and heating drive such reversible transition due to the competitive complexation as evidenced by 2D NOESY 1 H NMR and isothermal titration calorimetry as well as X‐ray diffraction. The present work describes a straightforward way to obtain switchable PPR hydrogels triggered by a compatible stimulus of CO2 . These stimuli‐responsive PPR hydrogels have potential applications as biomaterials. Abstract : A facile CO2 ‐responsive supramolecular hydrogel without any functionalization is developed through the disassembly–reassembly of the polypseudorotaxane hydrogel of poly(ethylene glycol) and α‐cyclodextrins triggered by adding a CO2 ‐responsive compound 2‐aminobenzimidazole. By subsequent treatments of CO2 and heating for this ternary system, reversible sol‐gel and gel‐sol transitions are observed.